Global error bounds for mixed Quasi-Hemivariational inequality problems on Hadamard manifolds. (1st September 2020) - Hung, Nguyen Van; Tam, Vo Minh; Pitea, Ariana
ABSTRACT: In this paper, we introduce and study a class of mixed quasi-hemivariational inequality problems on Hadamard manifolds (in short, (MQHIP)). Some regularized gap functions for (MQHIP) are proposed under suitable conditions. Finally, global error bounds for (MQHIP) in terms of regularized gap functions are derived by employing some strong monotonicity conditions and using the properties of Clarke's generalized directional derivative. The main results presented in this paper improve and generalize corresponding results in literature.